Services from the Healthcare and Social Security Agency (BPJS) at Bankrupt Hospitals - Suhendra, Yandi; Libet Astoyo, Libet Astoyo; Arman Lany, Arman Lany (Journal of Law, Politic and Humanities, 2025)
In Indonesia, there has been an increase in the number of hospitals declared bankrupt, which has a significant impact on the implementation of the National Health Insurance (JKN) managed by the Health Social Security Administration. Hospitals as BPJS strategic partners face challenges in fulfilling health service obligations due to financial pressures and Bankruptcy Legal status, which can threaten the rights of participants to obtain decent health services. This situation reflects the urgent need for legal mechanisms that protect the rights of participants and ensure the sustainability of health services in the midst of economic and legal dynamics. This study aims to examine the obligations of health services to BPJS Kesehatan participants in hospitals that are experiencing bankruptcy, and analyze the legal basis that governs it. This issue is important considering that there is a potential conflict of interest between the hospital bankruptcy process and the obligation of sustainable health services to BPJS Kesehatan participants. This study uses normative juridical method by reviewing relevant regulations, such as Law No. 24 of 2011 on BPJS, Law No. 40 of 2004 on National Social Security System, and Law No. 37 of 2004 on bankruptcy and PKPU and conceptual approach to analyze the legal obligations of hospitals in bankruptcy conditions in providing health services and protecting the rights of BPJS Health participants. The results showed that the obligation to provide health services to BPJS Health participants remained based on the principle of protection of the right to health as mandated in the legislation. This study recommends the need for special legal protection mechanisms and coordination between the bankruptcy curator, BPJS Kesehatan, and the government to ensure the continuity of health services in hospitals experiencing bankruptcy